Relative biological effectiveness of carbon ions for local tumor control of a radioresistant prostate carcinoma in the rat - Peschke, Peter; Karger, Christian; Scholz, Michael; Debus, Jürgen; Huber, Peter E. (International journal of radiation oncology, biology, physics, 2011)
PURPOSE: To study the relative biological effectiveness (RBE) of carbon ion beams relative to X-rays for local tumor control in a syngeneic rat prostate tumor (Dunning subline R3327-AT1). - METHODS AND MATERIALS: A total of 198 animals with tumors in the distal thigh were treated with increasing single and split doses of either (12)C ions or photons using a 20-mm spread-out Bragg peak. Endpoints of the study were local control (no tumor recurrence within 300 days) and volumetric changes after irradiation. The resulting values for D(50) (dose at 50% tumor control probability) were used to determine RBE values. - RESULTS: The D(50) values for single doses were 32.9 ± 0.9 Gy for (12)C ions and 75.7 ± 1.6 Gy for photons. The respective values for split doses were 38.0 ± 2.3 Gy and 90.6 ± 2.3 Gy. The corresponding RBE values were 2.30 ± 0.08 for single and 2.38 ± 0.16 for split doses. The most prominent side effects were dry and moist desquamation of the skin, which disappeared within weeks. - CONCLUSION: The study confirmed the effectiveness of carbon ion therapy for severely radioresistant tumors. For 1- and 2-fraction photon and (12)C ion radiation, we have established individual D(50) values for local tumor control as well as related RBE values.
Available online 8 October 2010
Gesehen am 25.10.2022